Quality Assurance Analysis Internal Analytical Phase Of Urine Microalbumin Examination In Patients Hemodialisa - Juraijin, Denny (IKesT Muhammadiyah Palembang, 2025)
Background: Internal quality assurance is a preventive and monitoring activity carried out by each laboratory regularly to prevent errors/deviations from occurring or reduce errors so that correct examination results are obtained. Internal laboratory quality strengthening is carried out to control the results of laboratory examinations every day, and to find out that the internal laboratory quality strengthening activities, including the quality of precision and accuracy of laboratory results, will increase. In routine urine examinations, it is necessary to carry out internal and external quality control. In carrying out internal quality urine examinations, qualified ATLM officers are required, in other words, officers who have passed DIII/DIV education by the Decree of the Minister of Health of the Republic of Indonesia number 42 of 2015. Professional competence is obtained through education, training, and apprenticeship over a long and quite difficult period, the learning is carefully designed and implemented strictly, and ends with a certification exam. Objective: This study is to analyze the internal quality control of the analytical phase of urine microalbumin examination in hemodialysis patients. Output: This research analyzes the internal quality control of the analytical phase of microalbumin examination in hemodialysis patients, applies quality control to laboratory examinations, and obtains accurate and well-validated results. Improvements to teaching. materials will be published in the accredited national journal Sinta 3. The proposed research is in the form of a technological concept formulation and its application